MORPHOLOGICAL ANALYSIS BETWEEN PREFIX AND SUFFIX IN JACQUELINE HOWARD ARTICLE OF CNN - Risna Dewi Nurhayati; Lukman Arif Rahman (IKIP Siliwangi, 2024)
This study aims to find out the types of suffixes and to find out the frequently used prefixes and suffixes in CNN’s Jacqueline Howard's article titled